Determinants of Success and Failure in Entrepreneurship: A Literature Review - Nina Himawati (Journal of Business Improvement, 2024)
Entrepreneurship is the equivalent of the word entrepreneurship in English. Meanwhile, in Indonesia, it is called entrepreneurship. The word entrepreneur comes from the French word entrepreneur which means adventurer, risk taker, contractor, businessman (a person who undertakes a particular job), and a creator who sells his creations. Business success is a company's ability to create and distribute wealth and its differentiation, which is usually related to innovation. A business is said to be successful if it makes a profit because profit is the goal of people doing business. Failure is a normal thing in business. Statistics prove that almost 50% of start-up businesses fail, especially in the first five years of turning the wheels of business. However, failure can be an early milestone on the way to success. To achieve success, a person needs management, or a sequence of actions as strategic steps so that the expected target is achieved